Proceedings of the 35th IEEE/ACM International Conference on Automated Software Engineering 2020
DOI: 10.1145/3324884.3416623
|View full text |Cite
|
Sign up to set email alerts
|

Test automation in open-source Android apps

Abstract: Automated testing of mobile apps has received significant attention in recent years from researchers and practitioners alike. In this paper, we report on the largest empirical study to date, aimed at understanding the test automation culture prevalent among mobile app developers. We systematically examined more than 3.5 million repositories on GitHub and identified more than 12, 000 non-trivial and real-world Android apps. We then analyzed these non-trivial apps to investigate (1) the prevalence of adoption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…This team reported that, the higher level of test automation maturity is associated with shorter release cycles and better product quality in the CI context. [33] 2020 As noted in Table 2, in all studies [27,33,34,35,28,37,38,39,30,32] that have observed how test automation maturity affects product quality, the findings verified the positive impact. These studies view product quality as to which extent a software product free from defects during the quality assurance process or in the production environment.…”
Section: Test Automaton Maturity; Release Cycle; Product Qualitymentioning
confidence: 59%
See 2 more Smart Citations
“…This team reported that, the higher level of test automation maturity is associated with shorter release cycles and better product quality in the CI context. [33] 2020 As noted in Table 2, in all studies [27,33,34,35,28,37,38,39,30,32] that have observed how test automation maturity affects product quality, the findings verified the positive impact. These studies view product quality as to which extent a software product free from defects during the quality assurance process or in the production environment.…”
Section: Test Automaton Maturity; Release Cycle; Product Qualitymentioning
confidence: 59%
“…One school of viewpoint states the negative relationship of test automation maturity and product quality with test automation effort. Studies [33,28,37,30,31], which hold this view, have observed the increased effort to develop and execute more rigorous automated tests in attaining higher product quality. Experience study [36] reported that the direct effect of test automation maturity on test automation effort is negative.…”
Section: Test Automaton Maturity; Release Cycle; Product Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another study oriented towards Android applications was executed by Lin et al, where more than 3.5 million GitHub repositories were analyzed, and they identified more than 12,000 non-trivial and real-world Android apps [22]. They observed that only 8% of applications have any automated tests, only 6% unit tests and UI testing is less adopted than unit testing (4%).…”
Section: Related Workmentioning
confidence: 99%
“…To aid the developers with development of concurrent software, Android provisions several new concurrency constructs in the form of libraries, such as AsyncTask and Looper. Nevertheless, concurrency is a major source of confusion for developers [26] and remains among the top 5 reasons for defects in Android apps [51].…”
Section: Introductionmentioning
confidence: 99%